2009
DOI: 10.1007/s11120-009-9491-6
|View full text |Cite
|
Sign up to set email alerts
|

Probing of photosynthetic reactions in four phytoplanktonic algae with a PEA fluorometer

Abstract: High-resolution light-induced kinetics of chlorophyll fluorescence (OJIP transients) were recorded and analyzed in cultures of diatoms (Thalassiosira weissflogii, Chaetoceros mulleri) and dinoflagellates (Amphidinium carterae, Prorocentrum minimum). Fluorescence transients showed the rapid exponential initial rise from the point O indicating low connectivity between PS II units and high absorption cross-section of PS II antenna. Dark-adapted dinoflagellates revealed capability to maintain the PS I-mediated re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…All of these things taken together could turn Chl a fluorescence into a indecipherable signal, but thanks to the development of specific protocols, and by using complementary techniques, the different effects can be separated, turning Chl a fluorescence into a powerful tool for the study of photosynthesis: quenching analysis (Bradbury and Baker 1981; Quick and Horton 1984; Schreiber et al 1986), JIP test (Strasser and Strasser 1995; Strasser et al 2004), non-photochemical quenching (NPQ) (Demmig and Winter 1988; Horton and Hague 1988), electron transport rate (ETR) (Genty et al 1989; Krall and Edwards 1990), rapid light curves (RLCs) (White and Critchley 1999; Ralph and Gademann 2005), flash-induced fluorescence (Robinson and Crofts 1983; de Wijn and van Gorkom 2001; Bouges-Bocquet 1980, Ioannidis et al 2000), dark-adaptation kinetics of OJIP transients (Bukhov et al 2001; Schansker et al 2005), Chl a fluorescence and photoacoustic spectroscopy (Buschmann and Koscányi 1989; Snel et al 1990; Allakhverdiev et al 1994; Bukhov et al 1997), Chl a fluorescence and 820-nm absorbance/transmission (Klughammer and Schreiber 1994; Schansker et al 2003), Chl a fluorescence and delayed fluorescence (Goltsev et al 2012; Kalaji et al 2012a), imaging (Nedbal and Whitmarsh 2004; Hideg and Schreiber 2007; Lichtenthaler et al 2007; Gorbe and Calatayud 2012), the actinic light wavelength dependence of photosynthesis (Schreiber et al 2012) and more recently attention has been paid to statistic aspects of the measurements of parameters (e.g., Bussotti et al 2011a). The photosynthetic literature is huge with many topics studied such as plant breeding (Baker and Rosenqvist 2004; Kalaji and Pietkiewicz 2004; Kalaji and Guo 2008), seed vigor and seed quality assessment (Jalink et al 1998; Dell’Aquila et al 2002; Konstantinova et al 2002), fruit and vegetable quality determination and postharvest processing control (Merz et al 1996; Nedbal et al 2000), senescence (Adams et al 1990a; Kotakis et al 2014), climate change effects (Ashraf and Harris 2004) and a variety of algae (Gorbunov et al 1999; Antal et al 2009; Grouneva et al 2009). Furthermore, Chl a fluorescence measurements have been used for monitoring plant stresses (Guidi and Calatayud 2014), such as photoinhibition (Sarvikas et al …”
Section: Question 1: What Is Chlorophyll a Fluorescence And Why Do Wementioning
confidence: 99%
“…All of these things taken together could turn Chl a fluorescence into a indecipherable signal, but thanks to the development of specific protocols, and by using complementary techniques, the different effects can be separated, turning Chl a fluorescence into a powerful tool for the study of photosynthesis: quenching analysis (Bradbury and Baker 1981; Quick and Horton 1984; Schreiber et al 1986), JIP test (Strasser and Strasser 1995; Strasser et al 2004), non-photochemical quenching (NPQ) (Demmig and Winter 1988; Horton and Hague 1988), electron transport rate (ETR) (Genty et al 1989; Krall and Edwards 1990), rapid light curves (RLCs) (White and Critchley 1999; Ralph and Gademann 2005), flash-induced fluorescence (Robinson and Crofts 1983; de Wijn and van Gorkom 2001; Bouges-Bocquet 1980, Ioannidis et al 2000), dark-adaptation kinetics of OJIP transients (Bukhov et al 2001; Schansker et al 2005), Chl a fluorescence and photoacoustic spectroscopy (Buschmann and Koscányi 1989; Snel et al 1990; Allakhverdiev et al 1994; Bukhov et al 1997), Chl a fluorescence and 820-nm absorbance/transmission (Klughammer and Schreiber 1994; Schansker et al 2003), Chl a fluorescence and delayed fluorescence (Goltsev et al 2012; Kalaji et al 2012a), imaging (Nedbal and Whitmarsh 2004; Hideg and Schreiber 2007; Lichtenthaler et al 2007; Gorbe and Calatayud 2012), the actinic light wavelength dependence of photosynthesis (Schreiber et al 2012) and more recently attention has been paid to statistic aspects of the measurements of parameters (e.g., Bussotti et al 2011a). The photosynthetic literature is huge with many topics studied such as plant breeding (Baker and Rosenqvist 2004; Kalaji and Pietkiewicz 2004; Kalaji and Guo 2008), seed vigor and seed quality assessment (Jalink et al 1998; Dell’Aquila et al 2002; Konstantinova et al 2002), fruit and vegetable quality determination and postharvest processing control (Merz et al 1996; Nedbal et al 2000), senescence (Adams et al 1990a; Kotakis et al 2014), climate change effects (Ashraf and Harris 2004) and a variety of algae (Gorbunov et al 1999; Antal et al 2009; Grouneva et al 2009). Furthermore, Chl a fluorescence measurements have been used for monitoring plant stresses (Guidi and Calatayud 2014), such as photoinhibition (Sarvikas et al …”
Section: Question 1: What Is Chlorophyll a Fluorescence And Why Do Wementioning
confidence: 99%
“…A rapid non-sigmoidal increase of the O-J step has been related to physiological characteristics such as a low energetic connectivity between PSII units and a high absorption cross-section of PSII antennae (Antal et al 2009). Thus, similarly in C. reinhardtii, the more rapid and less sigmoidal O-J fluorescence rise for cells grown in the N-and NPstarved condition (higher V j and M O ) could suggest that under N limitation, the PSII units are energetically isolated and with a large absorption cross-section of their antenna (Lavergne and Trissl 1995;Trissl 2003;Antal et al 2009;Solovchenko et al 2013). However, the increase of absorption cross-section of PSII antenna indicated by the O-J step is contradicted by the lower Chl a cell content and the expectation therefore of smaller PSII antennae.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence amplitude of the IP step (ΔF IP ) was calculated according to Ceppi et al (2012). Non-photochemical quenching (NPQ) was calculated from the decline of fluorescence after the P step up to 6 s, according to the equation reported in Antal et al (2009). A full list of the fluorescence parameters examined is given in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum photosynthetic electron transport rate changed with the N/P ratios in the urea treatments, the more concentrated treatments had the higher rETR values at the beginning. Moreover, the φPSII and F v /F m values were pretty low at the N/P ratio of 4:1, which might be due to the decrease of the efficiency of electron transport from the primary quinone-type acceptor (QA -) to QB (Antal et al, 2009;Petrou et al, 2012), or to the decline of the D 1 protein concentration, which is low under nutrient deficient conditions (Steglich et al, 2001). Huang et al (2014) also reported that low urea concentrations did not sustainably promote the growth, photosynthesis and toxin production of the M. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%